Prophylactic effect of herbal extracts on LPS-induced inflammatory response in rat hepatocytes - Mohamed S. Abdel-Latif; Alaa Hegazy; Sofia Khalil; Doaa Ghareeb (International Journal of Phytomedicine, 2017)
Background: Liver is participating in the clearance of the infectious agents mainly by Kupffer cells and to a lesser extent by sinusoidal endothelial cells and hepatocytes. Lipopolysaccharide (LPS), a major component of bacteria cell wall, is an endotoxin translocated from the gut; inducing oxidative stress and acute inflammation in hepatocytes. This study aimed to highlight the prophylactic effect of naturally occurring products (B. vulgaris and C. vulgaris) against LPS-induced toxicity. Methods: RT-PCR was performed using RNA extracted from rat hepatocytes as template to determine the gene expression of COX-2, i-NOS and TNF-α. Results: B. and C. vulgaris showed a noticeable improvement in maintaining COX-2, i-NOS and TNF-α at their basal expression level; even under LPS stimulation. However, the efficacy of C. vulgaris was better than B. vulgaris. In conclusion, LPS-induced inflammatory response to rat hepatocytes could be inhibited by B. and C. vulgaris as naturally occurring prophylactics.